Financial condition analysis ın municipalities: a case of turkey - ÖZKUL, Fatma; ALKAN, Betül Şeyma (My University, 2017)
This study included the analysis of prepared comprehensive financial statements with the transition to accrual-based accounting system from cash-based accounting system in the public institutions in 2006. In Turkey, there is no specific method developed to the goals of public institutions. GASB 1 Reporting Model, which is a model developed in the USA, and is not yet used in Turkey, has been applied by taking financial statements data of the Istanbul Metropolitan Municipality. The study was carried out using the institution’s balance sheets and statement of financial performance for 2006-2014. Using ratios developed in the model, the financial condition of institution was measured from four different aspects: cash solvency, budget solvency, long-term solvency, and service-level solvency, and the results were analyzed. The purpose of the study is the implementation of financial analysis methods to have a public sector accounting information system that will achieve a financial structure which can measure, evaluate and develop the financial condition of public institutions by decision-making and that will contribute to the efficient and comprehensible use of the produced information by decision- makers in Turkey.
Keywords: Accounting,Municipality,Financial Condition